A new Dasypodini armadillo (Xenarthra: Cingulata) from San Gregorio Formation, Pliocene of Venezuela: affinities and biogeographic interpretations - Cordeiro de Castro, Mariela (2014)
We describe Pliodasypus vergelianus gen. et sp. nov., a Dasypodini armadillo from the middle Pliocene of Venezuela (Vergel Member, San Gregorio Formation). Although scarce, the remains are remarkable because of their geochronologic proximity to the main phase of Great American Biotic Interchange (GABI). The cladistic analysis conducted reveals that Pliodasypus groups with Dasypus and both are sister taxa of Propraopus, whereas Anadasypus is at a basal position. With respect to the records of tribe Dasypodini, after its oldest representative (Anadasypus, middle and late Miocene), the chronologically subsequent form is Pl. vergelianus (middle Pliocene), followed by Dasypus bellus in higher northern latitudes (late Pliocene), and then by widespread occurrences in the Pleistocene of North America (D. bellus) and South America (Propraopus, Dasypus punctatus, and Dasypus novemcinctus). Thus, we infer that Dasypus differentiated in the late Pliocene at low latitudes in the northern South America. It leads to two alternative hypotheses of dispersal: (a) some early Dasypus remained cryptically in South America until the Pleistocene, whereas others dispersed to North America between 2.2 and 2.7 Ma, or (b) they dispersed to North America subsequently to the emersion of the Panamanian isthmus and D. bellus differentiated there; later, during the Pleistocene, D. bellus entered South America and experienced speciation. The same process of re-ingression has been proposed to other xenarthrans, breaking with the traditional assumption that the GABI was unidirectional.